Development of software package for determining efficiency of energy saving devices and technologies in production process of enterprise - A. A. Komyakov; A. V. Ponomarev; V. V. Erbes (Омский научный вестник)
The article is devoted to the development of a software module that allows continuous monitoring of the energy efficiency of the production process, as well as to determine the actual efficiency of the implemented electrical installations, modern energy saving devices and technologies based on fuzzy neural network models of the production process. The software module implements statistical processing of data on power consumption and the amount of work performed and convenient mechanisms for working with neural network models of the technological process.